2022
DOI: 10.1371/journal.pone.0273658
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Young, Deadly, Syphilis Free multi-media campaign in remote Australia

Abstract: Introduction Since 2011, remote Australian Aboriginal and Torres Strait Islander communities have experienced an outbreak of infectious syphilis, with young people aged 15–29 years over-represented in notifications. The Young Deadly Syphilis Free multi-media campaign was implemented in 12 remote regions in four Australian jurisdictions over nine months from 2017–2018. Campaign components included television and radio advertisements, social media posts, and health promotion resources available via a dedicated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…A study carried out by D’Coasta et al (2022) to evaluate the impact of syphilis public health campaign messaging in remote parts of Australia found that, at least for the younger demographics (age 15 to 29 years), multi-media modalities deemed be the most effective included television, Facebook, and websites on the Internet. These were reported as the most popular sources of campaign exposure routes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out by D’Coasta et al (2022) to evaluate the impact of syphilis public health campaign messaging in remote parts of Australia found that, at least for the younger demographics (age 15 to 29 years), multi-media modalities deemed be the most effective included television, Facebook, and websites on the Internet. These were reported as the most popular sources of campaign exposure routes [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Aboriginal participants were less likely to have heard of syphilis than non-Aboriginal respondents, despite notification rates being 5.6 times higher in this population group, 8 and the existence of Aboriginal-focused STI public health campaigns such as "Young, Deadly, Free." 23 Overseas-born respondents who had recently migrated to Australia also demonstrated poorer awareness *Missing data were excluded from the tables, so not all denominators will add to up 2018. Participants were able to skip questions they did not want to answer.…”
Section: Discussionmentioning
confidence: 99%
“…Of concern, we identified that some priority populations had particularly low awareness and/or knowledge about syphilis. For instance, Aboriginal participants were less likely to have heard of syphilis than non-Aboriginal respondents, despite notification rates being 5.6 times higher in this population group, 8 and the existence of Aboriginal-focused STI public health campaigns such as “Young, Deadly, Free.” 23 Overseas-born respondents who had recently migrated to Australia also demonstrated poorer awareness of syphilis than Australian-born respondents. People from culturally and linguistically diverse backgrounds are identified as a priority population in the Fourth National STI Strategy because of a high prevalence of STIs and low STI knowledge among some culturally and linguistically diverse groups and additional barriers to accessing sexual health care 13…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have addressed the perspectives of health personnel regarding the problems that would be affecting STI care, 2,3 especially in the most vulnerable populations in Latin America 4 . For this reason, this research addresses the limitations for the management of STIs in Peruvian indigenous pregnant women, based on the answers of midwives who work in Quechua‐speaking indigenous communities.…”
Section: Limitation N = 108 %mentioning
confidence: 99%